Comparative Performance of Soccer Teams of Different Age Groups - Andriy Kolosov; Serhii Voitenko; Viktor Kostiukevych; Tetiana Vozniuk; Maksym Perepelytsia; Nataliia Svirshchuk; Tamara Chernyshenko (OVS LLC, 2022)
The study purpose is to establish differences in the joint activities of soccer teams of different age. Materials and methods. Psychological methods for indicators of joint activity of sports teams were used. Statistical analysis was performed using non-parametric analysis of variance (Kruskal-Wallis H-test). The study involved 105 soccer players, including 37 boys aged 15-18, 45 juniors aged 19-21 and 23 adult athletes aged 22 and over. Results. In the young soccer players, group interaction, intellectual communication, psychological compatibility, as well as indicators of real and reflective group subjectivity are higher than in the adult and junior teams. The levels of group organization, diligence and success in performing sports tasks are dominant in the adult teams. At the same time, the integrative characteristic of joint sports activities is group efficiency, which is presumably the most pronounced in adults, thus characterizing the processes within the mental organization of joint activities of soccer players. It is the result of their cooperation, a transformed form of external teamwork. Conclusions. The organization of joint mental activity differs in different age groups. This affects the formation and development of intra-group position of the athletes, influencing their optimal involvement in the team in the performance of designed or creative functions. Keywords: soccer players, efficiency, interaction, subjectivity, organization.